2015
DOI: 10.1371/journal.pone.0123110
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles Release by Adipocytes Act as “Find-Me” Signals to Promote Macrophage Migration

Abstract: Macrophage infiltration of adipose tissue during weight gain is a central event leading to the metabolic complications of obesity. However, what are the mechanisms attracting professional phagocytes to obese adipose tissue remains poorly understood. Here, we demonstrate that adipocyte-derived microparticles (MPs) are critical “find-me” signals for recruitment of monocytes and macrophages. Supernatants from stressed adipocytes stimulated the attraction of monocyte cells and primary macrophages. The activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 49 publications
1
88
0
2
Order By: Relevance
“…Corresponding to these changes in glucose tolerance, we have previously reported that macrophage (F4/80 positive cells) infiltration in the epididymal AT is increased at 2 weeks of HF diet and becomes significantly higher after 6 weeks on HF diet compared to lean controls [7, 28, 29]. In addition, we have recently reported that sadEVs may contribute to the initiation of inflammation in AT by recruiting macrophages [15]. Our current results demonstrate that increase in circulating EVs strongly correlate with the development of glucose intolerance (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Corresponding to these changes in glucose tolerance, we have previously reported that macrophage (F4/80 positive cells) infiltration in the epididymal AT is increased at 2 weeks of HF diet and becomes significantly higher after 6 weeks on HF diet compared to lean controls [7, 28, 29]. In addition, we have recently reported that sadEVs may contribute to the initiation of inflammation in AT by recruiting macrophages [15]. Our current results demonstrate that increase in circulating EVs strongly correlate with the development of glucose intolerance (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Supplementary Table 1 lists all of the proteins identified in sadEVs generated by stressing adipocytes with the free fatty acid palmitic acid, a treatment that results in hypertrophy of adipocytes and significant production and release of EVs [15]. The most abundant proteins include proteins involved in translation, carbohydrate and lipid metabolism, cytoskeleton (e.g., clathrin, tubulins and annexins), extracellular matrix (e.g., fibronectin), ribonucleoproteins, and nucleosomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether this mechanism also contributes to caspase-1-induced MP release in our E10d + 1B model required further studies. In addition, activation of the caspase apoptotic pathway (caspase-3 and caspase-8) promotes MP release in several types of cells, including neutrophils (37), adipocytes (38), and hepatocytes (21). It will be interesting to investigate whether caspase-1 activation of pyroptosis, a type of programed cell death that is different from apoptosis (39), also contributes to MP formation and release.…”
Section: Shown Scale Bar: 100 μM Arrows Indicate Mpo+ Cells (D-h) Wmentioning
confidence: 99%